2019
DOI: 10.1002/jia2.25234
|View full text |Cite
|
Sign up to set email alerts
|

Re‐reading of OraQuick HIV‐1/2 rapid antibody test results: quality assurance implications for HIV self‐testing programmes

Abstract: Introduction Scale‐up of HIV self‐testing ( HIVST ) will play a key role in meeting the United Nation's 90‐90‐90 targets. Delayed re‐reading of used HIVST devices has been used by early implementation studies to validate the performance of self‐test kits and to estimate HIV positivity among self‐testers. We investigated the stability of results on used devices under controlled conditions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…This effect has previously been reported with a high incidence of true non-reactive results changing to weak positive when undergoing delayed reading of rapid antibody tests for HIV. 17 We therefore strongly advise against any use of lateral flow serological assays in home testing programmes that involve non-expert reading of cassettes or return postage of samples for evaluation at extended time intervals.…”
Section: Discussionmentioning
confidence: 99%
“…This effect has previously been reported with a high incidence of true non-reactive results changing to weak positive when undergoing delayed reading of rapid antibody tests for HIV. 17 We therefore strongly advise against any use of lateral flow serological assays in home testing programmes that involve non-expert reading of cassettes or return postage of samples for evaluation at extended time intervals.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the rst study in a French-speaking country in Africa to assess the practicability and effectiveness of UH versus DAH. A limitation of this study was that the re-reading by the research team of self-test device brought back by participants in sealed envelopes could have led to errors in interpreting the tests because other studies using the oral uid-based self-test have shown that delayed re-reading of used oral self-tests is not currently a valid methodological approach to ensure quality and monitoring and may overestimate true HIV-positivity [32]. Our protocol involving re-reading the Exacto ® HIV selftests was validated in a preliminary investigation that assessed the stability of 30 performed self-tests (15 positives and 15 negatives), and no changes in the results were found 72 h after use.…”
Section: Discussionmentioning
confidence: 99%
“…evaluated the OraQuick HIV‐1/2 antibody test kits for result stability post‐testing. They showed that while strongly reactive HIVST remained stable, 29% of initially non‐reactive kits converting to be weakly reactive false positive when read at least four days later, countering previous work which indicated OraQuick test kits were stable for up to a year . Re‐reading may be problematic and result in artificially inflated positivity rates; this finding led the WHO to recommend against any delayed readings of kits .…”
mentioning
confidence: 93%